Implementasi Model Pembelajaran Time Token untuk Meningkatkan Proses dan Hasil Belajar IPS Peserta Didik - Apdoludin, Apdoludin; Hamzah, Iri; Saleh, Khairul (INCOME: Indonesian Journal of Community Service and Engagement, 2025)
The main problem in this study is the low understanding of the concept of the material by students, students do not participate actively in the learning process, students do not understand the concept of the material being taught and low learning outcomes. The purpose of this study was to determine the improvement of the process and learning outcomes of students. The Time Token Model is a solution to the problems that occurred in class V as many as 11 students of SDN 025/II Muara Bungo, Bungo Dani District, Bungo Regency. The method used in this study is PTK. The results of the study showed that in cycle I the results of the assessment of the educator process obtained 59% while the results of the assessment of the student learning process in cycle I obtained 45% and the learning outcomes of students in cycle I were 55%. in cycle II the results of the assessment of the educator process obtained 83% while the results of the assessment of the student learning process in cycle II obtained 82% and the learning outcomes of students in cycle II were 82%. Conclusion with the application of the Time Token Learning Model Improves the Process and Results of Social Studies Learning of Class V Students of State Elementary School 025/II Muara Bungo, Bungo Dani District, Bungo Regency